A protocol for setting‐up robust hydrophobic interaction chromatography targeting the analysis of intact proteins and monoclonal antibodies. Issue 11 (24th December 2022) - Ewonde, Raphael Ewonde; Lingg, Nico; Eßer, Daniel; Eeltink, Sebastiaan
Abstract: Hydrophobic interaction chromatography (HIC) is a chromatographic technique that mainly targets the separation of biomolecules (intact proteins, monoclonal antibodies, etc.) based on the difference in surface hydrophobicity while applying non‐denaturing conditions. This protocol paper provides guidelines for setting‐up robust HIC analysis and considers the instrument configuration, mobile‐phase and sample preparation, as well as chromatographic conditions and settings. The separation of a mixture of intact proteins and monoclonal antibodies is demonstrated by applying conventional HIC conditions, that is, using a mildly hydrophobic (C4 ) stationary phase in combination with an inverse ammonium sulphate gradient dissolved in aqueous phosphate buffer. The effect of sample‐preparation conditions on sample breakthroughs is presented. Finally, good run‐to‐run repeatability (relative standard deviation < 2%) is demonstrated for five different columns obtained from three different column lots, considering chromatographic retention, peak width, peak area and column pressure.